Paramedics' experiences of administering fascia iliaca compartment block to patients in South Wales with suspected hip fracture at the scene of injury: results of focus groups. Issue 2 (15th February 2019) - Evans, Bridie Angela; Brown, Alan; Bulger, Jenna; Fegan, Greg; Ford, Simon; Guy, Katy; Jones, SIan; Keen, Leigh; Khanom, Ashrafunnesa; Longo, Mirella; Pallister, Ian; Rees, Nigel; et al.
Abstract : Objectives: To explore paramedics' experience of delivering fascia iliaca compartment block ( FICB) to patients with suspected hip fracture at the scene of injury. Design: Focus groups within a randomised controlled trial. Setting: Paramedics based at ambulance stations in the catchment area of one Emergency Department in South Wales, recruited and trained in a feasibility study about an alternative to routine prehospital pain management for patients with suspected hip fracture. Participants: 11 paramedics. Intervention: Paramedic-administered FICB to patients with suspected hip fracture. We randomly allocated eligible patients to FICB, a local anaesthetic injection directly into the hip region—or usual care, most commonly morphine - using audited scratch cards. Outcomes: Paramedics' experiences of administering FICB gathered through thematic analysis of interview transcripts by two researchers, one paramedic and one lay member. Results: Respondents believed that FICB was a suitable intervention for paramedics to deliver. It aligned with routine practice and was within people's capabilities. They said it took up to 10 minutes longer than usual care to prepare and deliver, in part due to nervousness and unfamiliarity with a new procedure. They praised the training provided but said they were anxious about causing harm by injecting into the wrong location. Confidence increased after one paramedic team successfully treated a patient for local anaesthetic toxicity. Reported challenges related to the emergency context: patients often waited many hours for ambulance arrival; moving patients exacerbated their pain; family and neighbours were present as paramedics administered treatment. Conclusions: Paramedics are willing and able to administer FICB to patients with suspected hip fracture before ambulance transport to hospital. Feasibility study findings will inform further research. Trial registration number: ISRCTN60065373 ; Pre results.